2023
DOI: 10.1002/pul2.12286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malnutrition on prognosis in patients with pulmonary arterial hypertension

Mitsutaka Nakashima,
Satoshi Akagi,
Kentaro Ejiri
et al.

Abstract: Pulmonary arterial hypertension is a life‐threatening disease that coexists with right heart failure. We evaluated the relationship between malnutrition and prognosis in patients with pulmonary arterial hypertension, as malnutrition is known as a prognosis determinant in chronic heart failure. We retrospectively reviewed data of patients with pulmonary arterial hypertension before treatment. The Geriatric Nutritional Risk Index, Prognostic Nutritional Index, and Controlling Nutritional Status scores on the day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(217 reference statements)
0
1
0
Order By: Relevance
“…[6][7][8][10][11][12][13][14] Recent studies have shown that some of these measures, as well as the degree of obesity, are associated with prognosis in pulmonary arterial hypertension and CTEPH. [15][16][17][18][19][20][21] However, the changes in the BMI and nutritional status of patients with CTEPH before and after BPA treatment have not been fully investigated. 22 CTEPH-induced deterioration of pulmonary circulation causes hypoxia.…”
mentioning
confidence: 99%
“…[6][7][8][10][11][12][13][14] Recent studies have shown that some of these measures, as well as the degree of obesity, are associated with prognosis in pulmonary arterial hypertension and CTEPH. [15][16][17][18][19][20][21] However, the changes in the BMI and nutritional status of patients with CTEPH before and after BPA treatment have not been fully investigated. 22 CTEPH-induced deterioration of pulmonary circulation causes hypoxia.…”
mentioning
confidence: 99%